Association of Serum Uric Acid with the Madras Diabetes Research Foundation-Indian Diabetes Risk Score (MDRF-IDRS) in Type 2 Diabetes Mellitus Patients - Tanmay Pawaskar; Saba Khan; Dhananjay Tiwari; Ahmad Merajul H. Inam; Roshan Alam; Mohammad M. Khan (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background: Elevated serum uric acid (SUA) indicates kidney malfunction in T2DM patients. The Madras diabetes research foundation—Indian diabetes risk score (MDRF-IDRS) is an established screening tool for T2DM. SUA and MDRF-IDRS both may be associated with the risk factors of diabetic nephropathy (DN) in T2DM patients. Aim: The aim was to find the association between SUA and MDRF-IDRS in T2DM patients. Material and Methods: In this case-control study, a total of 60 subjects (30 T2DM patients and 30 age-matched controls) were enrolled, aged between 35 and 65 years. Biochemical parameters and risk factors for DN were estimated by commercially available kit along with MDRF-IDRS risk factors. A P < 0.05 was considered statistically significant. Results: It showed that 60% of cases and 80% of controls were found between the age group of 35–49 years. Based on MDRF-IDRS, 33% of controls and 36% of cases were at high risk. Biochemical parameters and risk factors for DN were gradually elevated from low risk to moderate risk to high risk in cases and controls. The mean of WC has shown a significant difference between low risk to moderate risk to high risk in cases and controls (95% CI: 3.256–7.066, P < 0.001, d = 5.16 and 95% CI: 1.390–3.414, P < 0.001, d = 2.40, respectively). SUA has shown a significant positive correlation with WC and BMI among controls (r = 0.366, 95% CI: 0.007–0.642, P < 0.05 and r = 0.501, 95% CI: 0.171–0.729, P < 0.01, respectively). MDRF-IDRS has shown a significant positive correlation with WC (r = 0.845, 95% CI: 0.697–0.924, P < 0.01) among controls. Similarly, WC has shown a significant positive correlation with BMI and MDRF-IDRS among cases (r = 0.442, 95% CI: 0.097–0.692, P < 0.05 and r = 0.784, 95% CI: 0.591–0.892, P < 0.01, respectively). Conclusion: Results showed that risk factors for DN were significantly elevated in patients with T2DM compared to controls. SUA has demonstrated a significant positive association with WC, BMI, and MDRF-IDRS in controls. Similarly, WC has demonstrated a significant positive correlation with BMI and MDRF-IDRS among cases.